THERMAL DEFORMATION CONDITIONS FOR THE FORMATION OF HOLLOW CYLINDRICAL CAST IRON CASTING IN THE METAL WATER-COOLED FORM - E. I. Marukovich; V. F. Bevza; V. A. Popkovsky; V. P. Grusha (Литьë и металлургия, 2013)
An experimental and calculated thermal analysis of the bronze billets continuous casting plant is developed. Allowable thermal conditions for rolling-out are calculated.